P259 Seeking clickthroughs: using cell phone applications in preventing STDs. (14th July 2019) - Kachur, Rachel; Quilter, Laura; Boyette, Melissa; Brennan, Julia; Harvill, Jessica; Jones, Susan; Mclaughlin, Joe; Morawski, Bozena; Ridpath, Alison; Smith, Tracy; Tiffany, Amanda; Torrone, Elizabeth; et al.
Abstract : Background: Rates of reported early syphilis in Alaska increased over 300% between 2015 and 2018, with cases concentrated in men who have sex with men (MSM) that reside in the Anchorage/Mat-Su region. To better understand the epidemic, we surveyed at-risk Alaskan MSM about their syphilis knowledge, attitudes, and practices using a paper- and web-based survey. MSM were recruited through several avenues, including advertisements on two, popular geosocial-networking apps for gay, bisexual, and other MSM. We report on the relative efficiency in recruiting men through two different geosocial-networking apps. Methods: The geosocial-networking apps (App A and App B) were selected based on key-informant interviews. Identical ad text and imagery promoting the survey ran on each app for two weeks. The total number of times the ads were displayed (impressions), number of times users clicked on an ad (clicks), mean clickthrough rate (CTR; clicks/impressions), and costs for advertising on the two apps were estimated and compared. Results: App A had a total of 28, 642 impressions, and 904 clicks (daily range: 5–191). The mean CTR for App A was 5.45, at a cost of 0.32/click. App B had a total of 681 impressions, and 57 clicks. The mean CTR for App B was 8.37, at a cost of 12.28/click. Of 119 survey responses, 59 (50%) were online surveys, of which 32 (54%) reported hearing about the survey through the geosocial-networking apps ad. Conclusion: Recruiting MSM for surveys and prevention interventions through mobile apps is productive and may be cost-efficient. However, not all apps produce the same results. In our survey, App B was over 38 times more costly per click than App A. Programs should routinely explore the effectiveness and associated costs with utilization of app-based advertising. Disclosure: No significant relationships.